Effect of altitude and shade on production and physical attributes of Coffee in Gulmi, Syangja and Palpa districts of Nepal - Paudel, Manoj; Parajuli, Kiran; Regmi, Sudip; Budhathoki, Srijan (Journal of Agriculture and Natural Resources, 2021)
Coffee (Coffea spps.) is the second most traded commodity in the world after raw oil. Coffee is grown in mid hills of Nepal from an altitude of 700masl to 1500masl under different shade management practices. Nepalese coffee farmers grow coffee in a traditional way with almost zero application of inorganic fertilizers, pesticides and hence Nepalese coffee is popular as organic coffee or specialty coffee in the world. A study was carried out in three Coffee potent adjoining districts of Nepal: Gulmi, Syangja and Palpa. Ripe coffee cherries were harvested from every 200m altitude from 700masl to 1500masl under shade management and without shade management practices. Different physical attributes such as 1000 cherry weight, wet parchment weight, dry parchment weight, green beans weight, defected beans, and green bean diameter were observed. Production from each altitude level was recorded and highest production (7.04 kg per plant) was obtained from an altitude of 900-1100masl . The highest 1000 cherry weight (1297.17g) and the highest green bean weight (450.33 g) were obtained from 900-1100masl. Under no shade management, number of defected beans were 98 per 1000 beans whereas it was 64 under shade. The interaction of altitude and shade management practice had significant effect upon production (P=0.035), 1000 cherry weight (P<0.001), dry parchment weight (P=0.049) and green bean weight (P<0.05). Coffee produced at an altitude of 900-1100masl under shade management practice were found to have higher production and of better quality with fewer defected beans whereas that produced at extreme lower of 700-900masl and extreme higher altitude of 1300-1500masl were found to have lower production and poor quality.